Co-exposure of polystyrene nanoplastics and ozone synergistically induced airway inflammation: Evidence and biomarkers screening - Xiaotong Jian; Xinyu Zhang; Shufan Chang; Yuan Xue; Pingping Shang; Yu Liu; Huaiyong Chen; Xiaolei Zhou; Wei Wang; Pengpeng Wang; Feifei Feng (Ecotoxicology and Environmental Safety, 2025)
Nanoplastics (NPs) or Ozone (O3) is related to chronic respiratory diseases and can be exposed to human as coexisting air pollutants. However, there is no report on respiratory effect of co-exposure to NPs and O3. In this study, C57BL/6 J mice were instilled with polystyrene nanoplastics (PS-NPs, 1.82 ×1011, 3.64 ×1011) intratracheally for 14 days and exposed with O3 (0.6, 1.0 ppm, 3 h/d), lung function and pathological changes were determined, and the interaction between PS-NPs and O3 on airway inflammation was calculated by factorial design analysis of variance and additive index. Then, transcriptomics and non-targeted metabolomics of lung tissue of mice were performed to screen the biomarkers. We found that co-exposure of PS-NPs and O3 could synergistically induce airway inflammation in mice, with the severest injury in 1.00 O3 + 1.82 × 1011 PS-NPs group. Moreover, linoleic acid metabolism and ABC transporters were the key pathways, and the interaction of 3 core metabolites (prostaglandin F2b, 20-HETE, PLP) and 3 core genes (Per2, Per3 and cyp3a13) were significantly related to the occurrence of airway inflammation in mice. To our knowledge, this finding is the first to uncover the synergistical effect and biomarkers of co -exposure to PS-NPs and O3 on airway inflammation.